2015
DOI: 10.14257/ijbsbt.2015.7.3.13
|View full text |Cite
|
Sign up to set email alerts
|

Critical Thinking Disposition, Professional Self-concept and Caring Perception of Nursing Students in Korea

Abstract: The purpose of this study was to determine the association among critical thinking disposition, professional self-concept, and caring perception in nursing students and to identify its effects on professional self-concept. 161 nursing students, who were freshmen and sophomores having performed no clinical practice in Seoul, participated in this study. The data were collected from September to December 2013 and the collected data were analyzed using descriptive statistics, Pearson's correlation coefficients, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
3
1
1
Order By: Relevance
“…This result represents a different result of Mwale OG et al, study [9], and one similar to the result of H.Y.Woo et al, study [10]. It can be seemed very different but there were common sense as it indicated in two studies, that would emphasize the need for this plan like overcoming the difficulties through vivid method.…”
Section: Resultscontrasting
confidence: 49%
“…This result represents a different result of Mwale OG et al, study [9], and one similar to the result of H.Y.Woo et al, study [10]. It can be seemed very different but there were common sense as it indicated in two studies, that would emphasize the need for this plan like overcoming the difficulties through vivid method.…”
Section: Resultscontrasting
confidence: 49%
“…This second category comprises articles relating to the assessment of critical thinking (30%, n = 71). Common assessments are the California Critical Thinking Disposition Inventory (and its Chinese version), the California Critical Thinking Skills, Critical Thinking Disposition Inventory (and its Chinese version), Critical Thinking Disposition Scale-Korean version and Watson–Glaser Critical Thinking Appraisal (Atay & Karabacak, 2012 ; Chen et al, 2010 ; Huang, Chen, Yeh, & Chung, 2012 ; Kaya & Yalniz, 2012 ; Kim, Moon, Kim, Kim, & Lee, 2014 ; Moattari, Soleimani, Moghaddam, & Mehbodi, 2014 ; Pai, Eng, & Ko, 2013 ; Pilevarzadeh, Mashayekhi, Faramarzpoor, & Beigzade, 2014 ; Suliman & Halabi, 2007 ; Woo & Tak, 2015 ; Zhang et al, 2017 ). Among the subscales of these instrument tools, low scores of truth-seeking, confidence, systematicity and inference are frequently reported in Chinese, Taiwanese, Korean, Turkish, Iranian and Pakistani medical and nursing students (Atay & Karabacak, 2012 ; Chen et al, 2010 ; Huang et al, 2012 ; Kaya & Yalniz, 2012 ; Kim et al, 2014 ; Mahmoodabad, Nadrian, & Nahangi, 2012 ; Moattari et al, 2014 ; Pai et al, 2013 ; Penjvini & Hejrani, 2015 ; Wong, 2007 ; Woo & Tak, 2015 ; Yeh, Chen, & Huang, 2009 ; Yildirim, Ozkahraman, Korkmaz, & Ersoy, 2011 ; Zhang & Lambert, 2008 ; Zhang, Li, Wu, & Chen, 2009 ; Zia & Dar, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…reported in Chinese, Taiwanese, Korean, Turkish, Iranian and Pakistani medical and nursing students(Atay & Karabacak, 2012;Chen et al, 2010;Huang et al, 2012;Kaya & Yalniz, 2012;Kim et al, 2014;Mahmoodabad, Nadrian, & Nahangi, 2012;Moattari et al, 2014;Pai et al, 2013;Penjvini & Hejrani, 2015;Wong, 2007;Woo & Tak, 2015;Yeh, Chen, & Huang, 2009;Yildirim, Ozkahraman, Korkmaz, & Ersoy, 2011;Zhang & Lambert, 2008;Zhang, Li, Wu, & Chen, 2009;Zia & Dar, 2019).…”
mentioning
confidence: 99%
“…Jeong (2015) found that critical thinking disposition was positively correlated with perspective taking (r=0.482, p<0.001), fantasy (r=0.227, p<0.001), and empathic concern (r=0.195, p=0.002) 17 . Woo & Tak, (2015) illustrated that critical thinking disposition positively correlates with caring perception (r=0.174, p=0.024) and professional self-concept (r=0.343, p=0.022) 18 . A similar study by Park, Chung, & Kim, (2016) demonstrated significant correlation between nursing competency and critical thinking disposition (r=0.59, p<0.001) and self-directed learning readiness (r=0.54, p<0.001) 19 .…”
Section: Discussionmentioning
confidence: 99%